Consumption of Iron and Vitamin C In Female Students at SMKN 3 Cimahi - Febia Muslikhatun Tiasmi; Cica Yulia; Ai Nurhayati (Universitas Pendidikan Indonesia (UPI), 2021)
Anemia is a condition when the level of hemoglobin (Hb) in the blood is low. In Cimahi City, the prevalence of anemia in junior and senior high school girls in Cimahi based on data from the Health Service was 70% in 2016. Anemia in adolescent girls is influenced by several factors including consumption patterns. The number of young women who follow a strict diet, consume more plant foods that contain little iron compared to animal foods, so that iron needs are not met and their nutritional intake is not balanced. The purpose of this study was to analyze the consumption of iron and vitamin c of female students of SMKN 3 Cimahi. This research uses a cross sectional study design, the method used in this research is descriptive quantitative. Data were collected by means of interviews using Food Recall instruments 2x24 hours and Food Frequency Questionnaires. The results showed that the average adequacy of iron and vitamin C of female students at SMKN 3 Cimahi was 11.44 mg/day and 36.99 mg/day. The consumption of iron and vitamin C did not meet the recommended amount. Lack of consumption of iron and vitamin C can cause a lack of iron absorption so that you are prone to anemia. Adolescents should pay attention to the intake of iron and vitamin C consumption a day to match the recommendations.